LIVESTOCK OWNERSHIP IN ENSURING RURAL HOUSEHOLD FOOD SECURITY IN PAKISTAN - A. Ali; M. A. Khan (Journal of Animal and Plant Sciences, 2013)
The current study focuses on the role of livestock ownership in ensuring rural household food security in Pakistan. For the study a comprehensive data were collected from the rice-wheat area of Pakistani Punjab. Three main districts of rice wheat area i.e. Gujranwala, Sheikhupura and Hafizabad were selected for the current study. Poisson regression analysis was carried out to estimate the determinants of livestock ownership. The impact of livestock ownership on household food security was estimated by employing the propensity score matching approach. The empirical results indicate that food security levels were higher in the range of 19-41 percent for the households having livestock ownership as compared to households having no livestock ownership. The policy implications of the study are that livestock ownership needs to be encouraged as it can help in ensuring rural household food security.
Keywords: Livestock Ownership; Food Security; Poisson Regression; Pakistan